Variations in Microbial Diversity and Metabolite Profiles of Female Landrace Finishing Pigs With Distinct Feed Efficiency - Wang, Zhixin; He, Yingzhi; Wang, Chuduan; Ao, Hong; Tan, Zhen; Xing, Kai (Frontiers in Veterinary Science, 2021)
To enhance pig production, feed efficiency (FE) should be improved. The mechanisms by which gut microbes affect FE in pigs have not been fully elucidated. To investigate the components and functional differences of the gut microbiota associated with low and high FE, bacterial assemblages were characterized using 16S rRNA sequencing, functional annotations were performed by shotgun metagenomics, and metabolomic profiles were made from Landrace female finishing pigs with low and high feed conversion ratios. Lactobacillus was enriched in the gut microbes of individuals with high FE, while Prevotella significantly increased in low-efficiency individuals, which might be linked to carbohydrate consumption and incomplete digestion. The activities of pathways involved in the metabolism of cofactors and vitamins were more intense in pigs with lower FE. There were also differences in pyruvate-related metabolism, such as phenylalanine and lysine metabolism. This suggests that pyruvate metabolism might be closely related to microbial fermentation in the large intestine, which in turn affects glycolysis. The study extends our understanding of how the gut microbiota are closely related to pig growth traits, and regulating the microbial composition could aid in improving FE in pigs. These results need to be validated using a larger pig cohort in the future.